2010
DOI: 10.5152/akd.2010.168
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of coronary blood flow in non-ischemic dilated cardiomyopathy with the TIMI frame count method

Abstract: Assessment of coronary blood flow in non-ischemic dilated cardiomyopathy with the TIMI frame count method Methods: This retrospective study included 62 patients with idiopathic dilated cardiomyopathy (34 men, 28 women; mean age 59.7±10.6 years) and 62 control subjects without dilated cardiomyopathy (28 men, 34 women; mean age 56.6±9.8 years). All patients and control subjects had angiographically proven normal coronary arteries. Dilated cardiomyopathy patients had a left ventricular ejection fraction <45%. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It has been reported that TIMI frame count was correlated with flow velocity measured with Doppler guidewire or transthoracic Doppler echocardiography during baseline conditions or hyperemia [16,17] and this measurement could be used as a surrogate marker for epicardial coronary blood velocity and microvascular status [18]. In patients with normal epicardial coronary arteries, high TFC values have been reported in small-vessel disease as early manifestation of atherosclerosis, in patients with metabolic syndrome, aortic stenosis, idiopathic dilated cardiomyopathy, chronic obstructive pulmonary disease or end-stage renal disease [19][20][21][22][23]. To date, there are no data concerning application of TFC method in the assessment of coronary blood flow in AF patients, and correlations between clinical and echocardiographic characteristics and mean TFC were not elucidated.…”
Section: Timi Frame Count and Its Associates In Af Patientsmentioning
confidence: 99%
“…It has been reported that TIMI frame count was correlated with flow velocity measured with Doppler guidewire or transthoracic Doppler echocardiography during baseline conditions or hyperemia [16,17] and this measurement could be used as a surrogate marker for epicardial coronary blood velocity and microvascular status [18]. In patients with normal epicardial coronary arteries, high TFC values have been reported in small-vessel disease as early manifestation of atherosclerosis, in patients with metabolic syndrome, aortic stenosis, idiopathic dilated cardiomyopathy, chronic obstructive pulmonary disease or end-stage renal disease [19][20][21][22][23]. To date, there are no data concerning application of TFC method in the assessment of coronary blood flow in AF patients, and correlations between clinical and echocardiographic characteristics and mean TFC were not elucidated.…”
Section: Timi Frame Count and Its Associates In Af Patientsmentioning
confidence: 99%